Safety and Efficacy of Eltrombopag and Romiplostim in Myelodysplastic Syndromes: A Systematic Review and Meta-Analysis - Meng, Fanqiao; Chen, Xiuqiong; Yu, Shunjie; Ren, Xiaotong; Liu, Zhaoyun; Fu, Rong; Li, Lijuan (Frontiers in Oncology, 2020)
Background and Aim: Many studies indicated that eltrombopag and romiplostim could improve hematopoietic function in patients with myelodysplastic syndromes (MDS), but their toxicity and efficacy were not known. This meta-analysis aimed to investigate the safety and efficacy of eltrombopag and romiplostim in MDS. Methods:A full-scale search strategy was used to search relevant published studies in PubMed, Embase, Web of Science, and the Cochrane Library until January 2019 using a random-effects model and the pooled risk ratio (RR) with 95% confidence interval (CI) as the effect indicator. Statistical analyses were performed using RevMan 5.3. Results:This meta-analysis included 8 studies comprising 1047 patients. A lower RR of overall response rate (ORR) (RR: 0.65; 95% CI, 0.47–0.9) and grade ≥3 bleeding events (RR: 0.36; 95% CI, 0.36–0.92) were observed after romiplostim and eltrombopag treatment compared with placebo. No difference in mortality, serious adverse events, platelet transfusion, hematologic improvement (HI), and AML transformation was observed. Conclusions:Thrombopoietin receptor agonists (TPO-RAs) romiplostim and eltrombopag were effective in reducing bleeding events, especially grade ≥3 bleeding events. However, it might reduce the ORR of MDS. Due to the limited treatment of MDS and the poor response to the drug, this may be a selection method for MDScombined with fatal bleeding, although further research is needed to confirm the effectiveness of this approach.